Implementation Of Good Governance Principles To Increase Library Service Capacity In Sungai Kerjan Kelurahan Office In 2020 - Mulia Jaya; Firmansyah Firmansyah (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2022)
This study describes bureaucratic transparency, participation, and the rule of law, as well as the impediments to the application of Good Governance principles at the Sungai Kerjan Village Office. The findings indicated that the application of Good Governance principles at the Sungai Kerjan Village Office was good, but it should be improved again because there are several indicators that make service delivery less than optimal. According to the findings of the study, the indicators of the factors that impede the application of good governance principles to increase the capacity of public services in the process of managing a Business Certificate (SKU) at the Sungai Kerjan Village Office, Bungo Dani District, are as follows: 1) Internal variables (factors from within). Lack of understanding of the apparatus on Good Governance principles The Kelurahan's implementation of Good Governance is still ineffective due to a lack of understanding of the principles of good governance. 2) External variables (factors come from outside) a lack of community involvement Participation is a sign of democracy when people are included in the development and implementation of a plan. as well as accept responsibility in accordance with one's maturity and level of obligation Complaint or criticism services via question cards have not been operating effectively. With the budget, the implementation of using their own personal laptops has not been liquidated. The implication of this research is that it is hoped that there will be an increase in the quality of the Human Resources (HR) workforce in providing services and improving facilities and infrastructure, allowing for better and more optimal service implementation at the Sungai Kerjan Village Office.